2000
DOI: 10.1097/00000374-200003000-00014
|View full text |Cite
|
Sign up to set email alerts
|

An Association Study Between Alcoholism and the Serotonergic Receptor Genes

Abstract: The study results suggest that these serotonergic receptor genes may not directly contribute to the etiology of alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…These studies were then filtered to ensure conformity with the inclusion criteria. One study (Himei and others 2000) was excluded because it was investigating the 294-Rsa1 polymorphism, rather than the polymorphisms analyzed in this meta-analysis. In the end, 18 studies, composed of 17 case-control (Cao and others 2011; Cigler and others 2001; Contini and others 2012; Gao and others 2011; Hasegawa and others 2002; Lee and others 2009; Proudnikov and others 2006; Sander and others 2000; Sun and others 2002; Ujike and others 2011; Wang and others 2012; Yuan and others 2005) and one HRR study (Hill and others 2002), met our criteria for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…These studies were then filtered to ensure conformity with the inclusion criteria. One study (Himei and others 2000) was excluded because it was investigating the 294-Rsa1 polymorphism, rather than the polymorphisms analyzed in this meta-analysis. In the end, 18 studies, composed of 17 case-control (Cao and others 2011; Cigler and others 2001; Contini and others 2012; Gao and others 2011; Hasegawa and others 2002; Lee and others 2009; Proudnikov and others 2006; Sander and others 2000; Sun and others 2002; Ujike and others 2011; Wang and others 2012; Yuan and others 2005) and one HRR study (Hill and others 2002), met our criteria for inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 21 studies, composed of 20 case-control studies and one HRR study (Hill et al 2002), met our criteria for inclusion. The 21 studies included five studies for European populations (Fehr et al 2001; Hill et al 2002; Parsian and Cloninger 2001; Wrzosek et al 2012), two studies for Hispanic samples (Polina et al 2009; Saiz et al 2008), and 14 studies for Asian populations (Cao et al 2002; Gao et al 2011; Himei et al 2000; Hwu and Chen 2000; Lee et al 2009; Li et al 2002; Nakamura et al 1999; Shao et al 2005; Terayama et al 2003; Tsunoka et al 2010; Wang et al 2001; Yang et al 2010). Among these studies, eight studies (Cao et al 2002; Gao et al 2011; Li et al 2002; Saiz et al 2008; Shao et al 2005; Wang et al 2001; Yang et al 2010) investigated heroin dependence or abuse; one study (Tsunoka et al 2010) investigated methamphetamine dependence; and the other 12 studies (Fehr et al 2001; Hill et al 2002; Himei et al 2000; Hwu and Chen 2000; Lee et al 2009; Nakamura et al 1999; Parsian and Cloninger 2001; Polina et al 2009; Terayama et al 2003; Wrzosek et al 2012) investigated alcohol dependence or abuse.…”
Section: Resultsmentioning
confidence: 99%
“…The same study was unable to detect any association between rs6318 and AD or alcohol abuse 72. Subsequently, the association between rs6318 and MHPG was not replicated,73 and several other studies failed to find a relationship between rs6318 and AD 61,74. Mottagui-Tabar et al (2004) reported that none of the four HTR2C promoter SNPs investigated nor the promoter microsatellite were shown to be associated with AD 75…”
Section: Htr2c and Substance Use Disordersmentioning
confidence: 97%